Effect of particle morphology on the electrochemical performance of hydrothermally synthesized NiMn2O4. (1st September 2020) - Saha, Samik; Roy, Atanu; Ray, Apurba; Das, Trisha; Nandi, Mahasweta; Ghosh, Basudev; Das, Sachindranath
Abstract: In this report, we have demonstrated the morphological effect on the electrochemical performances of hydrothermally synthesized NiMn2 O4 . Morphologies of the nanoparticles are varied using different surfactants and mineralizer during synthesis. Three different surfactants namely cetyl trimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS) and glucose and one mineralizer ammonium fluoride (NH4 F) are used all of which result in a spherically shaped particles with varying sizes. We have seen that addition of SDS results in an agglomeration of spherical nano-particles of NiMn2 O4 with good interconnection between them. Brunauer–Emmett–Teller (BET) surface area analysis confirms this sample offers highest surface area with mesoporous structure amongst all these samples. A specific capacitance of 1937 F g −1 is obtained for the same at 2 mV s −1 scan rate in 1 M aqueous Na2 SO4 electrolyte. A two-electrode asymmetric device has been fabricated using the sample as positive electrode and activated carbon as negative electrode. The device offers a specific capacitance of 270 F g −1 with excellent cyclic stability and good power and energy density. The superior performance of the device has been validated by demonstrating the capability of the device to harvest energy from a solar cell and to deliver the same through a LED. Graphical abstract: Image 1 Highlights: NiMn2 O4 has been synthesized using hydrothermal technique. Surfactants and mineralizer have been used separately to tune the morphology. A maximum specific capacitance of 1937 F g −1 is obtained in three electrode system. The two electrode asymmetric device shows excellent charge capability. The device has been used to store energy from commercial solar cell.